2015
DOI: 10.4206/agrosur.2015.v43n3-06
|View full text |Cite
|
Sign up to set email alerts
|

Escarabajos estercoleros nativos en Chile. Una revisión con énfasis en su ecología

Abstract: Dung beetles are crucial on the performance of different ecosystems, promoting several ecosystem services. In livestock production, these services are mainly related to the enhancement of soil fertility and the indirect biological control of parasites, through dung burial. Despite their known importance worldwide, in Chile the available scientific studies related to their ecology are scarce, despite the diversity of species found along the country. This work is an historical review of the available studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Second, we recovered fossil segments of the heads and legs – as discussed in the previous section – that are diagnostic for this genus and provided substantial evidence to distinguish between extinct and extant species of Scybalophagus . Finally, comprehensive knowledge of the Chilean Scarabaeoidea beetle fauna shows that only ten species (excluding the saprophagous Aphodiinae species) can be exclusively associated with dung resources: Homocopris punctatissimus (Curtis), H. torulosus (Eschscholtz), Frickius costulatus Germain, F. variolosus Germain, Megathopa villosa Eschscholtz, Scybalophagus rugosus , S. patagonicus , Taurocerastes patagonicus Philippi, Tesserodoniella elguetai Vaz‐de Mello & Halffter and T. meridionalis Vaz‐de Mello & Halffter (Vaz‐de Mello and Halffter, 2006; González‐Chang and Pinochet, 2015; Mondaca, 2023). Thus, based on knowledge of these dung‐dependent species and the multiple sampling efforts in south–central Chile (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we recovered fossil segments of the heads and legs – as discussed in the previous section – that are diagnostic for this genus and provided substantial evidence to distinguish between extinct and extant species of Scybalophagus . Finally, comprehensive knowledge of the Chilean Scarabaeoidea beetle fauna shows that only ten species (excluding the saprophagous Aphodiinae species) can be exclusively associated with dung resources: Homocopris punctatissimus (Curtis), H. torulosus (Eschscholtz), Frickius costulatus Germain, F. variolosus Germain, Megathopa villosa Eschscholtz, Scybalophagus rugosus , S. patagonicus , Taurocerastes patagonicus Philippi, Tesserodoniella elguetai Vaz‐de Mello & Halffter and T. meridionalis Vaz‐de Mello & Halffter (Vaz‐de Mello and Halffter, 2006; González‐Chang and Pinochet, 2015; Mondaca, 2023). Thus, based on knowledge of these dung‐dependent species and the multiple sampling efforts in south–central Chile (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, different studies have validated the use of animal manure to improve the soil's structure, physical condition, water retention, and fertility [52]. When mobilized by dung beetles, the presence of manure in pastureland is associated with greater soil fertility and indirect biological control of parasites in animals [53]. Research has also shown that the incorporation of animal manure is one of the main strategies of adaptation to climate change adopted by campesinos in different parts of the world [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive knowledge of the Chilean beetle fauna suggests that only a few species (nine) can be considered to be exclusively associated with dung resources ( González-Chang and Pinochet 2015 ). Thus, six species have been assigned to the Scarabaeidae family (excluding the saprophagous Aphodiinae species): two species belonging to Deltochilini tribe: Megathopa villosa Escholtz and Scybalophagus rugosus (Blanchard); and four species with uncertain taxonomic position ( incertae sedis sensu Tarasov and Dimitrov 2016 ): Tesserodoniella elguetai Vaz-de Mello & Halffter, T. meridionalis Vaz-de Mello & Halffter, Homocopris punctatissimus (Curtis), and H. torulosus (Escholtz) ( González-Chang and Pinochet 2015 ). The placement of the genus Homocopris in a suprageneric group requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, scientific expeditions and studies on biodiversity carried out in remote and still unexplored areas of the American continent, have made it possible to obtain a great deal of information about the natural history of certain specimens, alongside the description of an increasing number of new species. However, the genus Onthophagus has never been recorded from Chile ( Elgueta 2000 ; González-Chang and Pinochet 2015 ). Furthermore, the small number of fossil Onthophagus species described so far have been found in Europe, in sites dated from the middle to upper Paleocene (61.6–56 Ma) to middle Miocene (14–13.5 Ma), and a more recent North American fossil dated from the upper Pleistocene (0.068–0.004 Ma) ( Tarasov et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%